Therapeutic dilemma in patients with short cervices during pregnancy after conization - Suzuki S (Dove Medical Press, 2017)
Shunji SuzukiDepartment of Obstetrics and Gynecology, Japanese Red Cross Katsushika Maternity Hospital, Tokyo, JapanWe read the recent review article entitled “Prevention of preterm delivery: current challenges and future prospects” by van Zijl et al.1 However, they did not adequately discuss the prevention of preterm delivery in cases with a history of conization, or a cone biopsy of the uterine cervix.2,3 Performing a cervical cerclage has been common in the treatment of pregnant women with cervical insufficiency to prevent preterm delivery, as reported by van Zijl et al.1 However, the effect of prophylactic cerclage in women with a history of conization is little understood, because there are no prospective randomized controlled trials concerning the efficiency and risk of prophylactic cerclage in this subgroup of pregnant women.3–15 Table 1 summarizes the previous examinations concerning the effect of prophylactic cerclage in pregnancy after conization, including four English language articles searched using PubMed (Bethesda, MD, USA) and eight Japanese language articles searched using Igaku Chuo Zasshi® (NPO Japan Medical Abstracts society, Tokyo, Japan), with the key search terms of “cerclage” and “conization”.4–15 In these studies, statistical significances of the categorical variables were tested by Χ2 test (with Yates’s correction) or Fisher’s exact test. As shown in Table 1, there have been some small retrospective population-based cohort studies in this field. In an earlier study,3 cerclage has been recommended in pregnancies following excessive cone biopsy. However, some recent studies have suggested an association between local infection in cases of short cervices related to large cones and preterm labor in women with a history of conization.4–7 In these cases, sutures can act as a foreign body and lead to uterine irritability and contractions after a cerclage procedure.5–7 Moreover, some authors have reported a significant increase in pathologic flora in the vagina and cervix after cerclage leading to chorioamnionitis and preterm labor.16 Thus, prophylactic cerclage is used more sparingly in pregnancies following conization in recent years.5–7 Authors' replyMaud D van Zijl,1 Bouchra Koullali,1 Ben WJ Mol,2 Eva Pajkrt,1 Martijn A Oudijk11Department of Obstetrics and Gynaecology, Academic Medical Center, Amsterdam, the Netherlands; 2The Robinson Research Institute, School for Reproductive Health and Pediatrics, University of Adelaide, Adelaide, SA, AustraliaWe have read the response by Dr Suzuki with interest, and we agree with Dr Suzuki that our paper does not discuss preventive measures in cases with a history of conization. However, in our opinion, there is currently insufficient evidence of benefit from a cerclage in this specific group.It is known that women with a prior excisional procedure have a higher risk of preterm birth.1–3 As Dr Suzuki already points out, there are no randomized controlled trials that focus on the prevention of preterm birth in these high-risk women. So far, literature on the best strategy to prevent preterm birth after cone biopsy is lacking. Therefore, our paper does not give clear advice on how to treat these cases.View the original paper by van Zijl et al.